Pemanfaatan Media Pembelajaran Aplikasi Quizizz dalam Meningkatkan Motivasi dan Hasil Belajar Siswa SMK Migas Bumi Melayu Riau - Ramadhani; Suryani Putri, Esti; Syafi'i, Muhammad (JURNAL ARMADA PENDIDIKAN, 2023)
Education is one aspect that is very influential in the quality of human resources in a country. Improving the quality of education will improve the quality of human resources in the country. Success in carrying out learning activities can be seen from the results achieved by students. One of the efforts made to see the success of learning activities is to use learning methods that can attract the attention of students. Learning methods that utilize current technological developments can be used to increase student motivation and learning outcomes, one of the methods that can be used is by using the Quizizz application as a learning medium that can attract students' attention. Quizizz is an application that can be used as a medium for learning activities. This application combines education, games and technology. The purpose of this study is to describe how the use of the Quizizz application affects student motivation and learning outcomes. This study uses observation and descriptive methods. The approach used is a qualitative approach with descriptive data. Descriptive data, namely data collected from research results using words. The results of research using Quizizz are very effective in the process of learning activities at SMK MIGAS Bumi Melayu Riau.